Support the Cuban and other Latin American people's just struggle against U.S. imperialism. [Articles, speeches etc. by Mao Tse-tung, Liu Shao-chi, a.o (Foreign Languages Press, 1961)
On the cover also: !Cuba sí, Yanquis no!